Histological Comparison of Lyophilized Amniotic Membrane, Tulle Gras Dressing and Topical Gentamicin on Acute Partial Thickness Wound : In Vivo Study - Raymond, Benni; Fadila, Srigunda Arisya; Rahmadian, Rizki; Tofrizal, Tofrizal (Frontiers on Healthcare Research, 2024)
Background: Partial thickness wounds refer to the damage that extends from the epidermis to the upper layers of dermis. This study aims to compare the histological regrowth of acute partial thickness wounds following application of lyophilized amniotic membrane, tulle grass dressing and topical gentamicin. This study aims to establish a standard approach for treating partial thickness wound. Methods: Three groups of Mus Musculus mice were used in our experimental study. Similar to harvesting split thickness skin grafts, partial thickness wounds are performed. The wound was then treated with lyophilized amniotic membrane, tulle grass dressing and topical gentamicin. Using the Scoring System for Histological Assessment of Wound Healing, the wound is histopathologically examined at day 14. In this study, One way Anova was used for statistical analysis. Results: Application of lyophilized amniotic membrane showed different histological characteristic of healing from other method, with p=0.001 it showed significance epidermal growth compared to topical gentamicin. Whereas dermal thickness were also better, accompanied by lower dermal collagen density. Amniotic membrane has a large source of stem cells and contains several growth factors which is important in the physiological process of wound healing and tissue regeneration. Conclusions: Characteristic of skin healing using lyophilized amniotic membrane showed rapid epidermal growth and gave impression of less fibrosis tissue, so that would be potential for better wound treatment especially for prevention of scar.